Near-term projection of Amazon rainfall dominated by phase transition of the Interdecadal Pacific Oscillation - Yi Liu; Wenju Cai; Yu Zhang; Xiaopei Lin; Ziguang Li (npj Climate and Atmospheric Science, 2024)
Abstract The Amazon basin experienced a prolonged drought condition during the 2010s, leading to a large-scale forest degradation destructive to ecosystems and human society. Elusive are issues as to whether the decadal drought is driven by external forcing or internal variability, and whether the drought will continue or recover soon. Using large ensemble simulations from a state-of-the-art climate model, here we find a negative-to-positive phase transition of the Interdecadal Pacific Oscillation (IPO) explains ~45% (~40–49%) of the observed decadal drought of Amazon rainfall since 2010, much greater than the role of external forcing (~12%). Constraining future IPO phase transition reduces the uncertainty by ~38% from a range of −0.73 to + 0.31 mm day−1 decade−1 to a range of −0.42 to + 0.23 mm day−1 decade−1, of the near-term Amazon rainfall projection before 2040 under a mid-intensity emission scenario. Thus, the IPO plays a crucial role in the post-2010 drying and the near-term rainfall projection.